Effect of different sources of phosphorus and sulphur on kharif groundnut (Arachis hypogaea L.): Effect of different sources of phosphorus and sulphur on kharif groundnut (Arachis hypogaea L.) - A K GHOTMUKALE; K U LANDE; D S MUTKULE; S S WAGHMARE (Journal of Oilseeds Research, 2020)
Significantly higher growth characters, yield attributes and seed yield were obtained due to 50 kg phosphorus supplied in the form of SSP + 5 t/ha FYM than 50 kg phosphorus supplied as DAP + 5 t/ha FYM.